Studi penataan pada tanaman lanskap jalan di bagian hilir Tukad Mati, Kelurahan Legian, Kecamatan Kuta, Kabupaten Badung - Dewi, Putu Candra Kusuma; Utami, Ni Wayan Febriana; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021, 2021)
This research is motivated by lack of arrangement on streetscape plantations at the downstream of Tukad Mati as well as on-site roblems found such as unfit existing plantations to streetscape planting standar and unsupported behavior of community surrounding which establish unideal streetscape condition i.e. littering waste to the river, congestion created from street vendors and unintended gathering place on the sidewalks. Therefore, this study aims to determine the appropriate arrangement for streetscape with focusing on plantations arrangement. Method used in this study was field survey by implementing observations, field measurements and documentations data collection technique. Data were analyzed with descriptive qualitative method by comparing streetscape suitability with regulation standards and literatures. Results were indicated that the streetscape has potency to develop by arranging the plantations. It can be achieved by following government regulation on standard of streescape. Based on current situation of the street, it found that the previous plan for tree selection were not ideal, so it need to adjust by selecting and planting quen crape myrtle trees (Lagerstroemia speciosa) to substitute the previous streetscape plantations plan. Then, this recommended species was used as the main concept for structuring streetscape plantation at the downstream of Tukad Mati. The concept for spatial arrangement with this new tress selection will providing comfortable space for the user and improving the quality of the physical and visual of the street.